Peran Mediasi Kepercayaan pada Pengaruh Kepemimpinan Melayani Terhadap Kinerja Karyawan PT Nesinak - Indra Setiawan; Muhamad Ekhsan (Jesya (Jurnal Ekonomi dan Ekonomi Syariah), 2020)
The purpose of this study was to examine and explain the effect of serving leadership on employee performance mediated by trust. This research is a quantitative descriptive. The data were collected using an instrument in the form of a questionnaire. The sample of this research is 75 employees of PT Nesinak's production department. The analytical method for testing the hypothesis in this study is Partial Least Square (PLS). The results showed that serving leadership had a positive and significant effect on employee performance, the trust had a positive and insignificant effect on employee performance, the trust had a positive and significant effect on employee performance, serving leadership had a positive and significant effect on employee performance through trust